Preparation and Application of Superhydrophobic Copper Mesh by Chemical Etching and In-situ Growth - Tong, Qilei; Fan, Zhenzhong; Wang, Biao; Liu, Qingwang; Bo, Yunhe; Qian, Liqing (Frontiers in Chemistry, 2021)
Oily sewage and floating oil in the ocean post a huge threat to the ecological environment, therefore, developing an efficient separation for oil/water mixtures is an urgent need. Currently, superhydrophobic materials exhibit excellent oil/water separation ability. In this study, a superhydrophobic copper mesh prepared by the chemical etching method and the in-situ growth method and the performance evaluation are introduced. The oxide layer on the surface of the copper mesh is first removed by pickling, and then immersed in FeCl3 solution for chemical etching to make the surface rough, stearic acid (SA) is used for in-situ growth to reduce the surface energy, a superhydrophobic oil-water separation copper mesh is obtained. The water contact angle (WCA) of the copper mesh is more than 160°. The copper mesh is chemically stable and can effectively adsorb floating oil and separate the oil-water mixture. After several oil-water separation experiments, the oil-water separation efficiency can still be above 98%. The effects of the concentration of FeCl3 and SA on the contact angle and oil-water separation efficiency are investigated, the results show that when the concentration of FeCl3 is 2% and SA is 1.5%, the WCA and oil-water separation efficiency are the largest. The research used a simple and environmentally friendly method to prepare the oil-water separation copper mesh, which has important application significance for water quality restoration.